Uji Fisikokimia, Antibakteri VCO Metode Pembuatan Berbeda pada Bakteri Staphylococcus Aureus Terhadap Luka Kronis - octo zulkarnain (Jurnal Gizi, 2020)
Wounds have slowed healing due to the formation of biofilms, which are the surface formation of bacterial cells that are covered by the polymeric substance. Staphylococcus aureus is a gram-positive bacteria that play a role in producing multilayer in biofilms and is very easy to resistant to antibiotics. VCO has the ability as an anti-bacterial content based on lauric acid and kaprat acid. This study used experimental Quasy with a mixed Methode method.  VCO is made with 3 methods, fishing, heating and mixing. Physicochemical test results show, the highest water content is found in the VCO heating, the same three-type weight, the highest peroxide number is in the VCO mixing and the highest free fatty acids on the VCO fishing. The results of antibacterial test with Kirby-Baur method There is no barrier zone from the 3 types of VCO. VCO used as a topical is VCO fishing. The results of a test analysis of the results of observations in patients as much as 15 people for 9 days in 3 treatments with chronic wounds obtained p < 0.05 (0.000) which means during the treatment that the wound condition is better.  Keyword : wounds, biofilms, Staphylococcus aureus, Physicochemical, VCO